Surviving in a hostile environment: an analysis of Zimbabwe’s foreign relations in 21st century international relations - Chigora, Percyslage; Dewa, Didmus (Academic Journals, 2014)
Zimbabwe, at the turn of the new millennium has received widespread condemnation particularly following the abandonment of the Structural Adjustment programmes (ESAP), intervention in Democratic Republic of Congo and with the implementation of the controversial land reform. The image portrayed abroad has been tattered because of reports of violence, instability and abandonment of the rule of law, which has created a serious challenge to modern developments on democracy and human rights. On one hand Zimbabwe has seemingly lost many friends especially those from the West and/or West controlled institutions. On the other hand, it has sought acquaintance with countries in the East and other developing countries. From such a standpoint the paper seeks to examine the causes behind this strain in relations between Zimbabwe and Western global actors. It is the aim of this paper to analyse the underlying causes and trace the origin of the strained relations with the Western world.